Kajian Pemberian Beras Analog yang Disubstitusi Glukomanan Porang (A. oncophyllus) Terhadap Profil Darah Mencit yang Diinduksi Aloksan - Melda Nurmaisari; Subeki; Sri Hidayati; Suharyono AS; Sussi Astuti (JURNAL AGROINDUSTRI HALAL, 2023)
Porang rice is made from porang tubers (Amorphopallus oncophyllus) and waxy cassava and has a high glucomannan content and has a low glycemic index (<55). Porang rice has a slightly brownish white color and has a shape like grains of rice and contains fiber which can help the digestive process in the body. Provision of porang rice against diabetic can improve blood profile. This study aims to determine the effect of giving rice from porang tubers pn the blood profile of diabetic mice. The experiment was arranged in a completely randomized design (CRD) with the treatment of observing blood profiles. The study consisted of 4 treatments with 6 replications. The data obtained was tested for uniformity using the Bartlett test and the additional data was tested with the Tuckey test. Furthermore, the data were anlyzed using variance to obtain an estimator of the varience and determine the effect of the treatment, then the data were analyzed using the BNT test at the 5% level. The results showed that the effect of giving porang rice on the blood profile of alloxan-induced mice gave values for the number of erythrocytes (7,48 million/mm3), leukocytes (5,55 thousand/mm3), hemoglobin (15,14 g/dL), hematocrit (32,28%).